Pemanfaatan Live Streaming TikTok sebagai Media Edukasi Trading Generasi Z pada PT TPFx - Nababan, Rafael Natal; Santoso, Bowo (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Social media platforms have great potential as a medium for financial education for Generation Z, despite still facing issues such as low trading literacy and the high spread of unreliable financial content. This Community Service activity is aimed at optimizing the use of TikTok's live streaming feature as a trading education tool for Generation Z through collaboration with PT TPFx. The material is delivered using an interactive approach that actively involves participants through discussions and question-and-answer sessions. The results of the activity show that the use of TikTok live streaming can improve basic understanding of trading and encourage Generation Z to learn trading in a more structured and responsible manner.